+0  
 
0
166
1
avatar

 

 

 

I need a quick refresher for this, i have in 4 hours and would like to see the rules in action in a simple problem like this.

Guest Nov 14, 2017
 #1
avatar
0

Find the derivative of the following via implicit differentiation:
d/dy(g(y)) = d/dy(16 (1/y - sqrt(y) + 2 y^3))

 

The derivative of g(y) is g'(y):
g'(y) = d/dy(16 (1/y - sqrt(y) + 2 y^3))

 

Factor out constants:
g'(y) = 16 d/dy(1/y - sqrt(y) + 2 y^3)

 

Differentiate the sum term by term and factor out constants:
g'(y) = 16 d/dy(1/y) - d/dy(sqrt(y)) + 2 d/dy(y^3)

 

Use the power rule, d/dy(y^n) = n y^(n - 1), where n = -1: d/dy(1/y) = d/dy(y^(-1)) = -y^(-2):
g'(y) = 16 (-(d/dy(sqrt(y))) + 2 (d/dy(y^3)) + (-1)/(y^2))

 

Use the power rule, d/dy(y^n) = n y^(n - 1), where n = 1/2: d/dy(sqrt(y)) = d/dy(y^(1/2)) = y^(-1/2)/2:
g'(y) = 16 (-1/y^2 + 2 (d/dy(y^3)) - 1/(2 sqrt(y)))

 

Use the power rule, d/dy(y^n) = n y^(n - 1), where n = 3: d/dy(y^3) = 3 y^2:
g'(y) = 16 (-1/y^2 - 1/(2 sqrt(y)) + 2 3 y^2)

 

Simplify the expression:
g'(y) = 16 (-1/y^2 - 1/(2 sqrt(y)) + 6 y^2) - Courtesy of "Mathematica 11 Home Edition"

Guest Nov 14, 2017

40 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.